Peran Bahasa Indonesia Sebagai Bahasa Pemersatu di Tengah Keberagaman Bahasa Papua Di Kota Sorong - astri, astri abbas; Vidya Rizzkia Amalia; Astri Abbas; Sutra Yanti; Muhammad Ridwan (El-Tarbawi : Jurnal Pendidikan Islam dan Humaniora, 2026)
Abstract Sorong City is a heterogenous urban area with exceptionally high ethnic and linguistic diversity, including indigenous Papuan communities such as the Moi and Kokoda tribes. This study aims to describe the linguistic diversity in Sorong City and examine the role of Indonesian as a unifying language in facilitating communication and social integration in public spaces. Employing a qualitative descriptive approach, data were gathered through field observations at Remu Market in Sorong City, alongside semi-structured interviews with selected informants. The results indicate that indigenous Papuans in Sorong City apply a well-balanced functional bilingualism pattern for social adaptation. In the domestic sphere, they consistently use their mother tongue to maintain tribal emotional bonds and preserve local cultural heritage. Conversely, when interacting in heterogenous public spaces such as Remu Market, the community utilizes Indonesian or the Papuan Malay dialect as a neutral economic and social bridge to prevent inter-ethnic misunderstandings. In conclusion, the dominance of the Indonesian language in urban areas does not necessarily erode local identity; rather, it functions as a cohesive tool for social integration. This equilibrium can be sustained through strengthening the family's role as the primary fortress for local language preservation, supported by local content curriculum policies in schools and traditional institutions. Keywords: Indigenous Papuans, Linguistic Diversity, Social Integration, Sorong City, Unifying Language.